Inequalities in Oral Health among Older Brazilians: A Cross-Sectional Analysis of a National Survey - Prado, Rosana Leal do; Saliba Garbin, Clea Adas [UNESP]; Saliba Moimaz, Suzely Adas [UNESP]; Saliba, Nemre Adas [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2018)
Objective: To investigate the association of tooth loss and periodontal disease with socioeconomic and demographic factors, the need for and use of health services, and the effect of oral health on the daily lives of older Brazilians. Material and Methods: We abstracted data from a nation-wide, representative, cross-sectional survey of 7619 Brazilians aged between 65 to 74 years. Poisson regression models were created to investigate associations between oral diseases and income, education level, gender, ethnicity, region of residence, and use of dental services; statistical significance was set at 5%. Results: The mean age of the 7619 subjects studied was 69 years (95% Confidence Interval, 68.9-69.1); 61.9% were women. Regarding ethnicity, 46.95% were White, 38.90% were Brown, 11.54% were Black and 2.53% belonged to other ethnic groups. Bleeding on probing or dental calculus was present in 26.67% of subjects, whereas LOA was present in 87.27%. The loss of at least one tooth was observed in 48.90% of subjects, while 47.03% were completely edentulous. Low educational status increased the prevalence ratio (PR) of all diseases (loss of attachment, PR=5.54; bleeding on probing, PR=3.93; tooth loss, PR=2.24; edentulousness, PR=3.34). The prevalence of tooth loss was 2.58 times higher in subjects who reported a monthly income of less than 301 USD. The effect on daily life was occasionally a protective factor and occasionally increased the likelihoods of diseases. Conclusion: These findings substantiate the association of socioeconomic conditions, demographic features, and use of dental services with bleeding on probing, presence of dental calculus, loss of periodontal attachment, tooth loss, and edentulousness among older Brazilian subjects.
Keywords: Oral Health; Health Status Disparities; Socioeconomic Factors; Tooth Loss